Estimating the extra costs of disability in European countries: Implications for poverty measurement and disability-related decommodification. (July 2020) - Morris, Zachary A; Zaidi, Asghar
It is widely accepted that people with disabilities incur additional expenditures on transport, heating, equipment and other items. In this article, we estimate the magnitude of these extra costs of living for adults with disabilities aged 50–65 across 15 countries of Europe using the Survey of Health, Aging, and Retirement in Europe (SHARE) data. Drawing on the standard of living approach of Zaidi and Burchardt, we compare the incomes required by households with and without adults with disabilities to obtain an equivalent standard of living. We advance upon this research by drawing on the cross-nationally harmonized data of adults aged 50+ from the SHARE. The results suggest that there are substantial extra costs of disability in these countries: around 44 percent of income for a household with an adult reporting a work-related disability and somewhat less than 30 percent of income for a household with an adult who receives disability benefits. Applying an equivalization scale based on these figures increases the overall poverty incidence rate, especially for households with disabled adult members. These findings thus have implications for analysing the entitlement and benefit levels for disability support programmes and for devising accurate poverty estimates concerning persons with disabilities.